Challenges of local administration in Algeria - Dahali, Rekia; Rahomni, Mohammad (Journal of Ecohumanism, 2025)
Due to the problems that are confronted by the local administration in Algeria for which it has been an obstacle to achieving the goals, and one of the major problems that are facing our local administrative system is the financial difficulties and the spread of corruption. For this reason, it would be necessary to modernize this system in order to provide a quality services to our citizens and this would happen only by activating the system’s vitality and making it more efficient. As well as avoiding slow delivery services as it is considered the core to our local administration. This necessitates the application of the digitization system because it has positive effects on the delivery services.